Sistem Mandiri Energi Pada Alat Deteksi Total Suspended Particulate - Gunawan, Muhammad Rifki; Andang, Asep; Aripin, Aripin (Majalah Ilmiah Teknologi Elektro; Vol 23 No 2 (2024): (Juli - Desember) Majalah Ilmiah Teknologi Elektro, 2025)
Many IoT systems depend on fossil energy. Therefore, with this research, an Energy Independent System was developed on the TSP Detection Tool, namely an IoT monitoring system that is able to fulfill its own energy without PLN energy. The purpose of this research is to create a TSP monitoring system that is able to fulfill its own energy for 24 hours. The research consists of collecting tools and materials, making and assembling the unit testing system, testing energy independence, testing wireless transmission of particulate data. The system consists of nodes, Gateway, DHT22 sensor, SEN1077 sensor, anemometer sensor, wind direction sensor, battery and mppt. The average energy generated during the test was 65.3WH, the energy generated each day tends to be different, this is due to the fact that the energy generated is different from the energy generated during the test. Tends to be different due to fluctuations in solar irradiation that are not constant. In sending data wirelessly to the android application, the data received is the same as the data sent, it's just that there is a delay in sending data Which is less than one second. Based on energy independent testing obtained there is a difference in energy in some tests, the system is still able to operate independently without PLN energy, due to the presence of Backup energy. In the research the system managed to fulfill its own energy but the system needs data transmission management so that the system can run in the long term.